Preference measurement in health - Bolin, Kristian; Blomquist, Glenn C. (Emerald, 2014)
Measurements of individual benefits of different health and medical interventions are fundamental for prioritizing among different alternative uses of resources in the healthcare sector. While psychometric measures do not necessarily provide information sufficient for assigning relative values to different health states, preference-based approaches produce measures that allow comparisons of such values. In this volume of the series of Advances in health economics and health services research, entitled Preference measurement in health, the papers cover altruism within families, differences in risk attitudes, and estimation of health benefits of food safety. Specific topics include efficiency and altruism, comparison of mother and daughter values of HPV vaccination for daughters, differences in risk attitudes between women and men, how context matters in valuing food safety programs, and valuation of health risks associated with pesticide use.
Keywords: Medical economics.; Medical care -- Evaluation.; elektronické knihy; electronic books